The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Vestibular Cognition 2017
DOI: 10.1163/9789004342248_015
|View full text |Cite
|
Sign up to set email alerts
|

The Moving History of Vestibular Stimulation as a Therapeutic Intervention

Abstract: Although the discovery and understanding of the function of the vestibular system date back only to the 19th century, strategies that involve vestibular stimulation were used long before to calm, soothe and even cure people. While such stimulation was classically achieved with various motion devices, like Cox's chair or Hallaran's swing, the development of caloric and galvanic vestibular stimulation has opened up new possibilities in the 20th century. With the increasing knowledge and recognition of vestibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“… As cited in Miller and Ngo and Grabherr et al., and in the text. Other reported effects of vestibular stimulation, particularly motion‐induced stimulation in neurodevelopmental disorders, are not listed here but can be found in Grabherr et al …”
Section: Stimulating the Common Core/acin With Caloric Vestibular Stimentioning
confidence: 91%
See 3 more Smart Citations
“… As cited in Miller and Ngo and Grabherr et al., and in the text. Other reported effects of vestibular stimulation, particularly motion‐induced stimulation in neurodevelopmental disorders, are not listed here but can be found in Grabherr et al …”
Section: Stimulating the Common Core/acin With Caloric Vestibular Stimentioning
confidence: 91%
“…Extrapolated to a clinical context, this finding is consistent with the excessive spending and risky financial decision‐making observed in mania. Vestibular stimulation also has (complex) effects on sleep in healthy subjects, and interestingly in the context of mania, historical records refer to the sedating and sleep‐promoting effects of rotation apparatuses …”
Section: Vestibular Neuromodulation Of Mania and Insightmentioning
confidence: 99%
See 2 more Smart Citations
“…While swings and rotating chairs have long been used with the aim of curing anxiety, mania, and depression [113], only two studies suggested that continuous body motions modify mood [114,115]. Interestingly, CVS also changes participants' responses to affective images [116 & ] and decisionmaking tasks [117 & ].…”
Section: Vestibular Modulation Of Emotionmentioning
confidence: 99%